Banki spółdzielcze jako lokalne instytucje finansowe na tle sektora bankowego w Polsce - Kata, Ryszard (Cooperative Banks as Local Financial Institutions Compared to Bank Sector in Poland, 2005)
The subject of the study is analysis of efficiency of activity and dynamics of development of cooperative bank sector in Poland in years 1996-2003. In the elaboration has been compared economical and financial results of cooperative banks with commercial banks to verily the hypothesis that local financial institutions - which are cooperative banks - can be effective on market so as commercial banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 412-419